PROFILING HERBAL MEDICINE USE BY TRANSTHEORETICAL MODEL AND PERCEIVED VALUE: A CASE STUDY OF YOUNG ADULTS IN MALAYSIA - Y. L. Adeline Tam (International Journal of Accounting, Finance and Business, 2021)
Herbal medicine market is experiencing tremendous growth in these few years. Young adults between 20 to 29 years old is the largest Malaysian consumer segment with high demand for health-related products. However, this segment is now switching to non-herbal products. Engaging young adults to herbal medicine consumption is important to avoid high dependency on older consumers for sales and customer base. This study aims to investigate, with person-centred approach, the heterogeneity profile of herbal medicine use among young adults using Transtheoretical Model and four perceived value dimensions, namely the quality, price, emotional, and social values. A self-administered questionnaire with verified instruments was designed for data collection. Convenient sampling was used to collect data in Johor Bharu and Kota Kinabalu. A total 363 samples were collected and examined with Two Step Cluster analysis in IBM SPSS. Findings confirmed that the prevalence of herbal medicine use among young adults is high. Findings also highlighted four clusters of herbal medicine use; whereby long-term users in the maintenance stage perceived the highest level of perceived value that is followed by short-term users in the action stage. Meanwhile, non-users in both precontemplation and preparation stages had below average level of perceived value. Emotional value is the most critical predictor of herbal medicine use. In conclusion, this study provides the basis to enhance the awareness of herbal as well as complementary and traditional medicine stakeholders on the perceived value of herbal medicine use. Marketers and complementary and traditional health practitioners, armed with this knowledge, could prepare and implement their marketing campaigns and health initiatives efficiently.